The Impact of Musyarakah Financing on Bank Muamalat's Revenue - Rahmadi, R. Alip Pratama; Lesmana, Indra; Permasih, Desty (Pascasarjana Universitas Pasundan, 2023)
Bank Muamalat as an Islamic financial institution operates without an interest system, so it is expected to be able to overcome the economic problems of Muslims through various financing schemes, including musyarakah financing. The greater the increase in musyarakah financing, the greater the potential for increasing bank income. However, not all financing has a significant impact on income. This study aims to analyze the effect of musyarakah financing on PT. Bank Muamalat's income during January-October 2019. The method used is quantitative with classical assumption test analysis techniques, simple regression, coefficient of determination, and t-test. The results of the study showed that musyarakah financing had a significant effect on Bank Muamalat's income with a correlation value of 0.921. The regression equation obtained is Y = 4.305 - 0.263X, which means that the effect of musyarakah financing on income is 92.1%, while 7.9% is influenced by other factors.